Nanocrystal Formulation to Enhance Oral Absorption of Silybin: Preparation, In Vitro Evaluations, and Pharmacokinetic Evaluations in Rats and Healthy Human Subjects - SeungRee Seo; Gwan-Young Kim; Min-Hwan Kim; Kyung Won Lee; Min-Jae Kim; Mansingh Chaudhary; Khadka Bikram; Taeheon Kim; Seungmok Choi; Heejin Yang; Joo Won Park; Dae-Duk Kim; et al. (MDPI AG, 2024)
Despite the various therapeutic benefits and high tolerance of orally administered silybin, poor water-solubility can be the main restrictive physicochemical feature, which results in low oral bioavailability in the absorption. A milk thistle nanocrystal formulation (HM40) was prepared using a modified wet-milling method. Comprehensive characterization was performed to determine the physical morphology, crystallinity, and physicochemical properties. The long-term stability was evaluated over 24 months. In vitro silybin release was assessed at pH 1.2 for 2 h, followed by pH 6.8 for 4 h. Finally, in vivo pharmacokinetic studies were conducted in rats and healthy human volunteers. HM40 exhibited a nanocrystal structure maintaining crystallinity and enhanced the solubility and dissolution of silybin compared to that of the raw material. The stability over 24 months revealed consistent surface morphology, particle size, silybin content, and solubility. In vitro release profiles indicated a significant increase in the silybin release from HM40. In vivo pharmacokinetic studies demonstrated that HM40 showed 2.61- and 1.51-fold higher oral bioavailability in rats and humans, respectively, than that of the reference capsule. HM40 formulation presents a stable and promising approach for the oral delivery of poorly water-soluble silybin, with the potential for use in pharmaceutical formulations containing milk thistle.